Antioxidant and oxidative enzymes, genetic variants, and cofactors as prognostic biomarkers of COVID-19 severity and mortality: a systematic review - Smail, Shukur Wasman; Ismail, Blnd Azad; Maghdid, Ivan Sdiq; Flaih, Abdullah Hayder; Janson, Christer (Frontiers in Molecular Biosciences, 2025)
Oxidative stress plays a pivotal role in the pathogenesis and progression of coronavirus disease 2019 (COVID-19). Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection disrupts redox homeostasis through excessive generation of reactive oxygen and nitrogen species, driving inflammation, endothelial dysfunction, and multi-organ injury. Serum oxidative and antioxidative enzymes, their genetic polymorphisms, and essential micronutrient cofactors have emerged as potential prognostic biomarkers for COVID-19 severity and mortality. Evidence indicates that imbalances in antioxidant enzymes such as superoxide dismutase, catalase, glutathione peroxidase, and glutathione reductase correlate with disease progression, while polymorphisms in GST, superoxide dismutase, CAT, and HO-1 genes may modify susceptibility and outcomes. Biomarkers of oxidative damage, including malondialdehyde, 8-isoprostanes, nitrotyrosine, and protein carbonyls, consistently associate with respiratory failure, intensive care admission, and mortality. Furthermore, micronutrients such as selenium, zinc, copper, manganese, and iron, which act as enzymatic cofactors, influence antioxidant defense capacity and clinical prognosis. Despite promising data, limitations in biomarker standardization and assay specificity remain key challenges for clinical translation. The aim of this systematic review is to integrate enzymatic, genetic, and cofactor-based biomarkers to enhance risk stratification, challenging and to improve prognostic modelling in COVID-19. A better understanding of these biomarkers may facilitate early identification of high-risk patients, guide therapeutic interventions, and ultimately improve clinical outcomes in COVID-19.